Cationic double K-hole pre-edge states of CS2 and SF6. Issue 1 (December 2017) - Feifel, R.; Eland, J.; Carniato, S.; Selles, P.; Püttner, R.; Koulentianos, D.; Marchenko, T.; Journel, L.; Guillemin, R.; Goldsztejn, G.; Travnikova, O.; Ismail, I.; et al.
Abstract Recent advances in X-ray instrumentation have made it possible to measure the spectra of an essentially unexplored class of electronic states associated with double inner-shell vacancies. Using the technique of single electron spectroscopy, spectra of states in CS2 and SF6 with a double hole in the K-shell and one electron exited to a normally unoccupied orbital have been obtained. The spectra are interpreted with the aid of a high-level theoretical model giving excellent agreement with the experiment. The results shed new light on the important distinction between direct and conjugate shake-up in a molecular context. In particular, systematic similarities and differences between pre-edge states near single core holes investigated in X-ray absorption spectra and the corresponding states near double core holes studied here are brought out.